Enhancing Science Learning Outcomes Through Active Learning with Pop-up Book Media in Fifth-Grade Elementary Students - Kudus; Nurrijal (Universitas Pendidikan Ganesha, 2024)
The low learning outcomes of students in science subjects pose a problem that requires innovative solutions in the learning process. This study aims to analyze the improvement of fifth-grade elementary students' learning outcomes in the science theme